Neural Circuit Reprogramming: A New Paradigm for Treating Neuropsychiatric Disease? - Tye, Kay M. (Neuron, 2014)
Theoretically, harnessing the brain’s own endogenous plasticity mechanisms could serve to alter both internal states and external behavior in a therapeutic manner.